The Effect of Andaliman Aromatherapy (Zanthoxylum acanthopodium Dc) on Pre-Delivery Anxiety - Juneris Aritonang; Sharfina Haslin; Ayu Agita Br. Surbakti (Poltekkes Kemenkes Palu, 2026)
Background: Anxiety is common in the third trimester. Globally, untreated anxiety affects 15–25% of pregnant women, with adverse effects on maternal health, labor, and fetal outcomes. Inhalation aromatherapy is a non-pharmacological intervention. Andaliman (Zanthoxylum acanthopodium DC), containing α-pinene, limonene, geraniol, citronellol, and geranyl acetate, shows therapeutic potential. This study aimed to evaluate the effect of inhalation aromatherapy with andaliman essential oil on pre-delivery anxiety in pregnant women. Method: This pre-experimental study used a one-group pretest–posttest design. Thirteen third-trimester primigravida women at PMB Rika Fadilah Marelan in 2024 were recruited using a total sampling approach. Anxiety was confirmed using the Hamilton Anxiety Rating Scale (HARS). Participants inhaled five drops of andaliman essential oil diluted in 20 ml of water for 15 minutes, twice in one week. Data were analyzed using the Wilcoxon signed-rank test. Result: The mean pre-test anxiety score was 30.08 ± 4.591 (range 23–37), indicating moderate to severe anxiety. After the intervention, the mean score decreased significantly to 19.85 ± 2.734 (range 15–24), corresponding to mild to moderate anxiety (p = 0.000). Conclusion: Inhalation aromatherapy with andaliman essential oil effectively reduced anxiety in pregnant women before delivery and may serve as a safe, practical, and culturally acceptable complementary intervention.